Epidemiological trends of infective endocarditis in a single center in Italy between 2003–2015. Issue 10 (3rd October 2018) - Ferraris, Laurenzia; Milazzo, Laura; Rimoldi, Sara Giordana; Mazzali, Cristina; Barosi, Alberto; Gismondo, Maria Rita; Vanelli, Paolo; Cialfi, Alessandro; Sollima, Salvatore; Galli, Massimo; Antona, Carlo; Antinori, Spinello
Abstract: Objective: Changes in the incidence, clinical features and microbiology of infective endocarditis (IE) observed in a single center in Italy were compared between the period 2003–2010 and 2011–2015. Methods: All cases of IE, defined as definite or possible according to the modified Duke criteria, observed at the 'L. Sacco' Hospital in Milan, Italy between 2003 and 2015 were retrospectively reviewed. Results: 366 episodes of IE were identified in 325 patients. The mean number of incident IE over the period 2003–2015 was 1.43 (range: 0.6–2.1) cases per 1000 admissions, with a significantly increasing trend from a mean of 1.28–1.72 cases per 1000 admissions/year in 2003–2010 and 2011–2015, respectively (+34%; p  = .04). Staphylococci remain the leading pathogens causing IE (29%) with a relative increase of methicillin-resistant Staphylococcus aureus between the two periods. Streptococci and enterococci account for 26% and 18% of IE, respectively. We found an increase in the proportion of cases due to enterococci (from 14% in 2003–2010 to 22% in 2011–2015). The rate of in-hospital mortality was 19%, similar in the two periods studied. Conclusion: The incidence of IE continuously increased in our cohort over the past decade and, along with the aging of the population, a raise in the incidence of health care-associated infections and a change in the distribution of prevalent pathogens were observed. Surgery was independently associated with higher in-hospital survival (AOR, 95% CI: 0.38, 0.19–0.74; p  = .005). A constant surveillance is required to guide the optimal management of the changing epidemiology of IE.